1984
DOI: 10.1007/bf00396763
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen mortality of tropical tree seedlings: experimental studies of the effects of dispersal distance, seedling density, and light conditions

Abstract: We present results of two experiments designed to identify the relative importance of dispersal distance, seedling density, and light conditions on pathogen-caused mortality of tropical tree seedlings. The field experiment on Barro Colorado Island, Panama, demonstrated that both an increase in dispersal distance and a decrease in seedling density reduce levels of damping-off disease among seedlings of Platypodium elegans, and that there is an interaction between the two factors. The results indicated significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
434
11
14

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(482 citation statements)
references
References 16 publications
23
434
11
14
Order By: Relevance
“…Nee 2003;Purves & Pacala 2005;Volkov et al 2005), the empirical evidence for the importance of pathogens has been growing, and recent interest in this mechanism is underpinned by a long history of field study in tropical forests (e.g. Augspurger 1984aAugspurger ,b, 1990Augspurger & Kelly 1984;Dalling et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nee 2003;Purves & Pacala 2005;Volkov et al 2005), the empirical evidence for the importance of pathogens has been growing, and recent interest in this mechanism is underpinned by a long history of field study in tropical forests (e.g. Augspurger 1984aAugspurger ,b, 1990Augspurger & Kelly 1984;Dalling et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Augspurger 1984aAugspurger ,b, 1990Augspurger & Kelly 1984;Dalling et al 1998;reviewed by Gilbert 2005). This body of work is extremely suggestive, but by no means conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…If effects of pathogens increase with plant density, pathogens have the potential to regulate host population size and alter spatial distributions (4,51). Several studies have demonstrated important density-dependent effects of disease in natural plant populations (18,21,55,75). Of course, plant survival, size, and growth rates also depend on plant density, and compensatory effects can alter the effect of disease on plant populations.…”
Section: Population Ecology and Geneticsmentioning
confidence: 99%
“…A morfologia das sementes, bem como o tipo de agente dispersor, influencia no processo, na distância alcançada pelos diásporos e na eficiência da dispersão, visto que, quanto mais distante da fonte dispersora, maior a probabilidade de estabelecimento e a contribuição para a dinâmica sucessional ( VAN DER PIJL, 1982;AUGSPURGER;KELLY, 1984). Visto que sementes resultantes da dispersão de áreas afastadas podem contribuir para a riqueza de espécies e a variabilidade genética das populações presentes no local, enquanto a dispersão restrita e a escassez de indivíduos produtores restringem a diversidade da comunidade florestal (CAMPOS et al, 2009).…”
Section: Introductionunclassified